Quechuisms in Moyobamba-San Martín Spanish - Alvarado Campos, Lizbeth (2010)
Every time we want to talk about Spanish it is difficult to find a point of balance and start, in this article we intend to explain that Amazonian Spanish is full of Quechuisms that enrich it and make it "peculiar". Historically, we have believed that only speakers who migrate to Lima and whose Ll is Quechua have this type of vocabulary, but we have not perceived in the same way the substratum that is produced in some parts of the country. In this case, in the jungle of Peru, specifically in Moyobamba-San Martin. What is produced in this work is a compilation of the most outstanding Quechuisms that were found in the field work in the aforementioned city. Subsequently, a morphological and semantic analysis of the same was made.